PHONETICS AND ACCENTS: EMBRACING DIVERSITY IN ENGLISH PRONUNCIATION IN SCHOOLS (Modern education and development, 2025)
This article discusses the importance of recognizing and addressing phonetic diversity and accents in English language pronunciation within school environments. It emphasizes that the accents students bring to the classroom reflect their cultural and regional identities, and that these differences can affect both teaching and learning. The article highlights the challenges educators face in teaching pronunciation, particularly in diverse classrooms where various accents and dialects are present.